Nilai-Nilai Pendidikan Islam dalam Tradisi Cucurak Masyarakat Kota Bogor - Pradika, Ayu Ratih Rizki (QuranicEdu: Journal of Islamic Education, 2025)
This research aims to analyze the values of Islamic education that exist in the Cucurak tradition in the Bogor city community. The research method used in this research is descriptive qualitative research method and supported by various related reference sources. This research shows that there are five values of Islamic education contained in the Cucurak tradition of the Bogor city community, such as the value of aqidah education through strong faith in Allah SWT, the value of amaliah education through almsgiving activities, the value of worship education through prayer and gratitude, the value of social education namely ukhuwah Islamiyah through friendship activities, and the value of preaching education through broadcasting Islam. The implementation of these Islamic educational values has a positive impact on the development of children and communities in Bogor City, making them responsible, empathetic, and noble individuals. Cucurak tradition is one of the effective ways to strengthen the values of Islamic education. This tradition not only functions as a social event, but also as an educational medium that teaches Islamic educational values.